Implementasi Kebijakan Pemberdayaan Dan Pengembangan Usaha Mikro Di Disnakerperinkopukm Kabupaten Kudus - Alhawariy, Saif (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
In the last two decades, micro enterprises have become the main pillars of the Indonesian economy which need to be supported and given wide opportunities as a form of protection and support in the development of the people's economy. In this regard, the Government of Kudus Regency has issued Regulation of the Regent of Kudus Number 2 of 2018 as a policy of empowering and developing micro enterprises in Kudus Regency. This study aims to analyze the implementation of policies and factors that support and inhibit the implementation of policies for empowerment and development of micro enterprises which is implemented. The method in this research uses a qualitative approach through the implementation theory of Edwards III. The research instrument used was the researcher himself using the data analysis technique model of Miles and Huberman. The Government of Kudus Regency, through Disnakerperinkopukm has organized empowerment and development of micro enterprises through data collection activities on micro enterprises, human resource development, facilitating financing sources, simplifying licensing services and facilitating marketing. Empowerment and development of micro enterprises that have been implemented by Disnakerperinkopukm still need improvement by taking into account the existing inhibiting factors, namely communication, resources and bureaucratic structures.